Chronicles - August 2009 - Tedjoworo, Hadrianus (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2009)
'Chronicles' is a journal column of "MELINTAS" which contains information about the various events, congresses, conferences, symposia, necrologies, publications, and periodicals in the fields of philosophy and theology.